# Simplify the following: 1. (a^2 + 2ab + b^2)/(a + b) 2. (2x^2 + x - 6)/(2x + 4)

*print*Print*list*Cite

Expert Answers

justaguide | Certified Educator

The two fractions to be simplified are:

1. (a^2 + 2ab + b^2)/(a + b)

use the relation (a + b)^2 = a^2 + 2ab + b^2

=> (a + b)^2/(a + b)

=> a + b

2. (2x^2 + x - 6)/ (2x + 4)

=> [2x^2 + 4x - 3x - 6]/(2x + 4)

=> [2x(x + 2) - 3(x + 2)]/(2*(x + 2))

=> (2x - 3)(x + 2)/2*(x + 2)

=> (2x - 3)/2

**This gives (a^2 + 2ab + b^2)/(a + b) = (a + b) and (2x^2 + x - 6)/ (2x + 4) = (2x - 3)/2**